2007
DOI: 10.1097/01.pas.0000213350.49767.46
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma of the Ocular Adnexa: A Study of 353 Cases

Abstract: We studied the cases of 353 patients with lymphoma involving the ocular adnexa diagnosed at the Massachusetts General Hospital between 1974 and 2005. The patients included 153 males and 200 females, aged 7 to 95 years, with a mean age of 64 years. In 277 cases, there was no known history of lymphoma. Seventy-six patients had a history of lymphoma, with the ocular adnexa being involved at relapse or with progression of the previously diagnosed lymphoma. The patients had marginal zone lymphoma (182 cases), folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
263
5
29

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(314 citation statements)
references
References 69 publications
17
263
5
29
Order By: Relevance
“…Most are primary tumours and are usually NHL of B-cell type: the most common primary lymphoma subtype occurring in the ocular adnexa is the low-grade malignant extranodal marginal zone B-cell lymphoma (EMZL), accounting for approximately two thirds of all ocular adnexal lymphomas. [5][6][7][8][9] Interestingly, the EMZL is also the most common primary lymphoma occurring in the choroid. 3 In the following review, the molecular pathologies of only DLBCL and EMZL will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Most are primary tumours and are usually NHL of B-cell type: the most common primary lymphoma subtype occurring in the ocular adnexa is the low-grade malignant extranodal marginal zone B-cell lymphoma (EMZL), accounting for approximately two thirds of all ocular adnexal lymphomas. [5][6][7][8][9] Interestingly, the EMZL is also the most common primary lymphoma occurring in the choroid. 3 In the following review, the molecular pathologies of only DLBCL and EMZL will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoma is the most common orbital malignancy, has a predilection for the elderly, and classically presents as painless proptosis or adenexal swelling over a duration of 5-7 months. 7,9 Non-Hodgkin's lymphoma is reported 11 to have an orbital presentation in 2.4% of all non-Hodgkin's lymphoma cases, while its prevalence is about 5% in systemic NHL. 9 According to Liang et al, 12 the incidence of secondary central nervous system lymphoma in a patient with orbital non-Hodgkin's lymphoma is 5.9%, and the most common form of central nervous system involvement in lymphoma is leptomeningeal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common type is either follicular, 12% to 23%, or DLBCL, 7% to 21%, depending on the study. [4][5][6][7][8][9] The frequency of ocular adnexal lymphoma with localization to the orbit has been cited as 54%. 5 It has been suggested that it may be more appropriate to analyze ocular 10 found that for secondary ocular adnexal lymphoma, follicular type is most common (33%-66%) followed by (in approximate decreasing frequency) multiple myeloma/plasmacytoma, lymphoplasmocytic lymphoma/immunocytoma, mantle cell lymphoma, DLBCL, Burkitt lymphoma, MALT lymphoma and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients present with disseminated disease, with lymphadenopathy, often with splenomegaly, and frequent involvement of the bone marrow. A minority of patients present with extranodal disease, most often involving the gastrointestinal tract 1 and occasionally Waldeyer ring 2 , but rarely involving other sites, such as the skin 3 or the ocular adnexa 4 . Nearly all patients with extranodal presentation of MCL will be found to have lymphadenopathy or more widespread disease on staging.…”
Section: Dear Editormentioning
confidence: 99%